181 Uterine and vaginal bacteria and cytokine profiles prior to artificial insemination between resulting pregnant and open postpartum beef cows. (28th November 2020) - Poole, Rebecca; Ault, Taylor B; Myer, Phillip R; Lear, Andrea; Pohler, Ky
Abstract: Numerous factors impact reproductive success in beef cattle; however, the presence and activity of bacteria in the reproductive tract and its effects on fertility is relatively unknown. The objective of this study was to evaluate the relationship between reproductive tract bacterial communities and cytokine profiles prior to timed-AI (TAI) and compare between resulting pregnancy status at d30. Sixty-eight beef cows, 80 ± 2.6 d postpartum at TAI, were synchronized and subjected to TAI on d0. Pregnancy was diagnosed via transrectal ultrasonography on d30. Uterine and vaginal flushes were collected on d -21 and -2 for bacterial DNA extraction to sequence the V1-V3 hypervariable regions of the 16S rRNA gene and to measure pro-inflammatory [interlukin-6 (IL-6)] and anti-inflammatory [IL-10 and transforming growth factor-beta (TGFβ)] cytokine concentrations using validated commercial ELISAs. Concentration data were analyzed using repeated measures in PROC MIXED of SAS and correlations were performed in SAS using Pearson correlation. There were no differences in cytokine concentrations by day or status x day. There were no differences in uterine IL-6 or IL-10 concentrations (P > 0.05). Uterine TGFβ concentrations were overall elevated in pregnant cows compared to open cows (72.6 vs. 13.7 ± 12.1 pg/mL, respectively; P < 0.05). On d -2, a positive correlation exists between TGFβ and the relative abundance of Actinobacteria in the uterus of pregnant cows (r=0.93, P = 0.02). There were no differences in vaginal IL-6 or TGFβ concentrations (P > 0.05). On d -2, vaginal IL-10 concentrations were elevated in open cows compared to pregnant cows (741.6 vs. 602.1 ± 47.0 pg/mL, respectively; P < 0.05) and a positive correlation exists between IL-10 and the relative abundance of Lentisphaerae in the vagina of pregnant cows (r=0.89, P = 0.04). These data suggest a possible relationship between bacterial communities and cytokines concentrations within the reproductive tract of beef cattle which may affect fertility.